DISABILITY ART EXPRESSION SEBAGAI WADAH KREATIVITAS DAN UPAYA MENGEMBANGKAN MOTORIK ANAK DISABILITAS DI PUSAT KEGIATAN BELAJAR MASYARAKAT WIDYA GUPTA - Larasati, M. S. P.; Yani, N. W. H.; Dwijayanti, D. A. M.; Pramita, D. A. R. A.; Andani, N. K. I. A.; Subrata, I. M. (Buletin Udayana Mengabdi; Vol 20 No 4 (2021): Buletin Udayana Mengabdi, 2022)
Persons with disabilities are people with limitations, be it physical, intellectual, motor, sensory, or mental for a long time and can experience obstacles in socializing or interacting with the environment and other citizens. This will certainly have a negative impact on the motivation and self-concept of persons with disabilities. The Widya Gupta Community Learning Activity Center (PKBM) is one of the schools in Bali that is intended to educate children with special needs, especially mentally retarded. However, many obstacles were found during the learning process. One of them is the lack of activities that can hone and develop children's neuromotor skills. Disability Art Expression which is an activity of traditional musical drama and painting for cutting can help overcome these problems.